PENGARUH STRUKTUR MODAL, RISIKO BISNIS DAN PERTUMBUHAN PENJUALAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Henni Valentina; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The company’s main objective is to maximize profit In improving the company's growth, this can be achieved by maximizing the financial performance company. But sometimes companies fail to enhance financial performance, which is one reason the company less careful in applying the factors that affect financial performance. This make the company’s performance is deemed poor by the investor. This study aims to examine the factors tha affect the financial performance that can bejudged from its capital structure, risk business and sales growth.This study uses secondary data from 9 sampled the financial statements of real estate and property companies and sampling using purposive sampling techniques. Classic assumption test in this study include normality test, multicollinearity, heterocedasticity test, autocorrelation test. Analysis of data using the multiple linear regression analysis, t-test, f, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 16.The results showed that the variables capital structure and risk business partially (t test) significantly affects the financial performance on the real estate and property companies in the Indonesia Stock Exchange (BEI), while the variable sales growth no significant effect on the performance finance on the real estate and property companies listed in the Indonesia Stock Exchange (BEI). The results of the study simultaneously (f test) showed a significant effect of the variable capital structure, risk business and sales growth on financial performance in real estate and property companies listed in the Indonesia Stock Exchange (BEI).Keywords:capital structure, risk business, sales growt, financial performance